DESEMPEÑO DE LOS EMPLEADOS DE LA COOPERATIVA DE AHORRO Y CRÉDITO JUAN PÍO DE MORA LTDA. DEL CANTÓN CALUMA PROVINCIA DE BOLÍVAR - Rojas Yanez, Martha Ibella (2018)
The evaluation of work performance is used as an instrument to improve human resources. The use of this system contributes to detect problems such as the integration of the employee in the institution in the position he occupies and the motivation he has to fulfill his tasks. That is why this research is carried out, establishing clear objectives to contribute to the improvement of the problem posed